The Effectiveness of Soy Milk and Cow’s Milk in Reducing Dysmenorrhea Pain: A Systematic Literatur Review - Retiningrum Retiningrum; Khamidah Achyar (Universitas Malahayati, 2026)
ABSTRACT Primary dysmenorrhea is a common menstrual problem among adolescent girls and is often associated with elevated prostaglandin levels, which trigger excessive uterine contractions and pain. Nutritional interventions are increasingly explored as non-pharmacological alternatives to reduce dysmenorrhea, with soy milk and cow’s milk being two commonly studied options. This study aims to synthesize existing evidence on the effectiveness of soy milk and cow’smilk in reducing primary dysmenorrhea among adolescents. Method: This study used a Systematic Literature Review(SLR) based on the PICO framework—population (adolescent girls), intervention (milk consumption), comparison (soy milk vs. cow’s milk), and outcome (reduction in dysmenorrhea pain). Articles published from 2015–2025 were searched in Google Scholar, Scopus (via Publish or Perish), and PubMed using Boolean keywords related to adolescents, soy milk, cow’s milk, and dysmenorrhea. Eligible studies included original research on adolescents with primary dysmenorrhea, clear milk dosage and duration, standardized instruments, and full text in Indonesian or English. After duplicate removal, screening, and full-text assessment, data on study characteristics, milk type, dosage, duration, and pain reduction were narratively synthesized. The initial literature search identified 1,007 journals from After going through a selection process, 4 journals met the requirements for analysis.The synthesis revealed that both soy milk and cow’s milk reduce primary dysmenorrhea based on NRS score, but soy milk showed more consistent effects. Consumption of 250 ml soy milk once daily for 1–2 days reduced pain by 3–4 NRS points. This benefit is supported by its nutrient content, where 250 ml soy milk contains 25–40 mg isoflavones (genistein daidzein and glycitein) and 200–300 mg calcium, or up to 500 mg in fortified products. Cow’s milk also reduced pain, with the best effect at 1,000 mg calcium/day (reduction of 4–5 NRS points), but its results were less stable. Overall, soy milk was more consistently effective than cow’s milk. Soy milk is a simple, safe, and effective non-pharmacological option for managing primary dysmenorrhea in adolescents, offering stronger and more consistent results than cow’s milk. It may be recommended as part of menstrual health education and daily nutritional intake for adolescent girls. Keywords: Soy Milk, Cow’s Milk, Primary Dysmenorrhea, Isoflavones, Calcium.